School Climate in the Engineering and Architecture Campus of a Mexican Public University: Students' Perspectives - María del Carmen Sandoval-Caraveo; Edith Georgina Surdez-Pérez; Abraham Gerardo Pérez-Sandoval (Universidad Nacional, Costa Rica, 2017)
The objective of this research was to identify the school climate that prevails in the students of the faculty of Engineering and Architecture in a Mexican public University. This study was conducted in response to a need to take care of the recommendations of the agencies evaluating the educational programs. It was done with a quantitative approach, of a descriptive and correlational type with non-experimental transactional design. The studied dimensions of the school climate were: organization structure, functionality, pedagogical practices, climate between peer interaction and satisfaction. The data were collected using a Likert scale questionnaire, with a reliability of .880 of Cronbach's Alpha coefficient and validity through confirmatory factorial analysis. The results obtained from the descriptive statistics pointed the favorable school climate in peer interaction and pedagogical practices. Organizational structure, however, was the lowest rated classroom climate dimension. ANOVA results showed significant statistical differences between the school climate and educational programs, the years that the students have remained in the university, the age and the school cycle. Pearson's correlation analysis revealed weak and negative correlation between school climate and student age.